Perubahan Sosial Masyarakat Desa Mulyoagung akibat Pembangunan Berwawasan Lingkungan melalui Tempat Pengolahan Sampah Terpadu (TPST) - Tesalonika Taradebora, Annisa Dwi Apsari Lely Viki Fatmala (Faculty of Social Science, Universitas Negeri Semarang, 2016)
Mulyoagung village of Malang is a semi-urban area is a destination for migrants bermukimnya. The increase in the volume of waste, especially domestic waste as a result of population increase can not be avoided. Garbage is not managed properly will harm the environment and humans. Waste problem that occurs in semi-urban area needs to be addressed through a sewage treatment facility. One attempt to address the problem of increasing the volume of waste in the village Mulyoagung done through the Integrated Waste Management (TPST). In addition to addressing the problems of garbage, TPST is also aimed at reducing poverty. This paper focuses on social change in communities around the village TPST Mulyoagung due to environmentally sound development through TPST. The method used is qualitative method with a naturalistic approach through interviews and observations. The results showed that people around TPSTthat previously did not work, now turned into workers TPST with a stable salary and able to meet their needs. But the existence of this TPST also had a negative impact of conflict between the parties TPST with local residents due to air polluted by garbage smell unpleasant.